Critical Evaluation of the Use of 3D Carbon Networks Enhancing the Long-Term Stability of Lithium Metal Anodes - Dou, Xinwei; Ding, Markus S.; Kim, Guk-Tae; Gao, Xinpei; Bresser, Dominic; Passerini, Stefano (Frontiers in Materials, 2019)
The lithium metal anode is considered the ultimate goal for pushing the energy density of lithium batteries to the theoretical maximum. “Coating” metallic lithium with protective (carbon) layers has been reported as a viable method to mitigate detrimental issues such as the dendritic lithium deposition and the continuous fracturing of the SEI layer. Herein, we propose a rather simple and economically efficient method employing carbonized filter paper position over the lithium metal electrode. After an initial spontaneous lithiation of the paper-derived, 3D carbon network, lithium plating/stripping experiments reveal highly stable and rather low overpotentials – particularly when replacing the standard organic carbonate based electrolyte by ionic liquids. The final volumetric energy density of this and the many comparable approaches so far reported in literature, however, remains to be carefully considered, as illustrated by a rather quick calculation.